Dynamic tax externalities and the U.S. fiscal transformation in the 1930s - Dirk Niepelt (University of Bern, Department of Economics, 2018)
We propose a theory of tax centralization in politico-economic equilibrium. Taxation has dynamic general equilibrium implications which are rationally internalized at the federal, but not at the regional level. The political support for taxation therefore differs across levels of government. Complementarities on the spending side decouple the equilibrium composition of spending and taxation and create a role for inter governmental grants. The model provides an explanation for the centralization of revenue, introduction of grants, and expansion of federal income taxation in the U.S. around the time of the New Deal. Quantitatively, it accounts for between 30% and 100% of the federal revenue share's doubling in the 1930s, and for the long-term increase in federal grants.
Keywords: D72; E62; H41; H77; 330; Fiscal policy; Federalism; Politico-economic equilibrium; Markov equilibrium; Public goods; Grants; Political Economy